VD_FINDINFO 217/II vom 26. Oktober 2009 - VD Tribunal cantonal (2009)
ACTION EN MODIFICATION, MODIFICATIONEN GÉNÉRAL, REVENU, OBLIGATION D'ENTRETIEN, ENFANT, RELATIONS PERSONNELLES | 273 al. 1 CC, 273 al. 3 CC, 273 CC, 275 al. 1 CC, 285 al. 1 CC, 286 al. 2 CC, 349 al. 2 CPC, 349 al. 3 CPC, 349 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 466 al. 1 CPC